2010
DOI: 10.1007/s11703-010-1049-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical fertilizer reduction and soil fertility maintenance in rice-fish coculture system

Abstract: In the long run, whether the use of chemical fertilizers could be reduced and soil fertility could be maintained through rice-fish coculture is less well known. At the pilot site of the rice-fish coculture system, which is one of the five "globally important agricultural heritage systems" (GIAHS), we conducted a 4-year study to compare fertilizer use, rice yield, and soil fertility in rice-fish coculture and rice monoculture. Based on the survey data from 21 villages, rice yield did not differ between rice mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…During our study, paired farmer fields in the survey and plots in field experiment 1 did not change in rice variety, irrigation scheme, and fertilization level (20,23) (Table S1). In addition, weather (temperature, precipitation, and relative humidity) during the rice growing seasons did not vary widely over the 6 y (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During our study, paired farmer fields in the survey and plots in field experiment 1 did not change in rice variety, irrigation scheme, and fertilization level (20,23) (Table S1). In addition, weather (temperature, precipitation, and relative humidity) during the rice growing seasons did not vary widely over the 6 y (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, high-yielding hybrid rice varieties have been dominant (20). The rice-fish coculture is considered a sustainable form of agriculture because it maximizes the benefits of scarce land and water resources by using relatively few chemical inputs, by producing both carbohydrate and protein products, and by conserving biodiversity (20)(21)(22)(23)(24). Despite other changes resulting from rapid development over the last 30 y in China, farmers continue to practice rice-fish coculture, in part because this system is an important component of traditional culture and local customs (e.g., rice-fish festivals) (21).…”
mentioning
confidence: 99%
“…In our 9-year field experiment, the average rice yields increased by 22.1% in the RFF farming system and 6.8% in the RF farming system compared to the yields of the RO farming system. However, a 6-year survey by Xie 26 showed that the rice yields between RF and RO farming systems did not differ. This is probably due to the application of pesticides to and large amounts of manure or chemical fertilizer in the RF and RO farming systems that were surveyed in Xie's study.…”
Section: Discussionmentioning
confidence: 98%
“…Research also indicates that these interactions control pests and diseases of rice plants [15][16][17][18], improve soil fertility [19], increase soil microbial activity [20], and change growth traits like root shape and lodging resistance [21]. Rice yield is increased, and the application of chemical fertilizers and pesticides is reduced by up to 30% [22]. Additionally, the ecological benefits increase as the diversity of field fish increases [23].…”
Section: Multi-values Of China-niahsmentioning
confidence: 99%